Nature vs. Nurture: Defining the Effects of Mesenchymal Stromal Cell Isolation and Culture Conditions on Resiliency to Palmitate Challenge - Boland, Lauren K.; Burand, Anthony J.; Boyt, Devlin T.; Dobroski, Hannah; Di, Lin; Liszewski, Jesse N.; Schrodt, Michael V.; Frazer, Maria K.; Santillan, Donna A.; Ankrum, James A. (Frontiers in Immunology, 2019)
As MSC products move from early development to clinical translation, culture conditions shift from xeno- to xeno-free systems. However, the impact of isolation and culture-expansion methods on the long-term resiliency of MSCs within challenging transplant environments is not fully understood. Recent work in our lab has shown that palmitate, a saturated fatty acid elevated in the serum of patients with obesity, causes MSCs to convert from an immunosuppressive to an immunostimulatory state at moderate to high physiological levels. This demonstrated that metabolically-diseased environments, like obesity, alter the immunomodulatory efficacy of healthy donor MSCs. In addition, it highlighted the need to test MSC efficacy not only in ideal conditions, but within challenging metabolic environments. To determine how the choice of xeno- versus xeno-free media during isolation and expansion would affect future immunosuppressive function, umbilical cord explants from seven donors were subdivided and cultured within xeno- (fetal bovine serum, FBS) or xeno-free (human platelet lysate, PLT) medias, creating 14 distinct MSC preparations. After isolation and primary expansion, umbilical cord MSCs (ucMSC) were evaluated according to the ISCT minimal criteria for MSCs. Following baseline characterization, ucMSC were exposed to physiological doses of palmitate and analyzed for metabolic health, apoptotic induction, and immunomodulatory potency in co-cultures with stimulated human peripheral blood mononuclear cells. The paired experimental design (each ucMSC donor grown in two distinct culture environments) allowed us to delineate the contribution of inherent (nature) versus environmentally-driven (nurture) donor characteristics to the phenotypic response of ucMSC during palmitate exposure. Culturing MSCs in PLT-media led to more consistent growth characteristics during the isolation and expansion for all donors, resulting in faster doubling times and higher cell yields compared to FBS. Upon palmitate challenge, PLT-ucMSCs showed a higher susceptibility to palmitate-induced metabolic disturbance, but less susceptibility to palmitate-induced apoptosis. Most striking however, was that the PLT-ucMSCs resisted the conversion to an immunostimulatory phenotype better than their FBS counterparts. Interestingly, examining MSC suppression of PBMC proliferation at physiologic doses of palmitate magnified the differences between donors, highlighting the utility of evaluating MSC products in stress-based assays that reflect the challenges MSCs may encounter post-transplantation.